The mammal collection (Mammalia) of the Zoological Museum of Uzhhorod National University - Kron, A.; Lugovoy, O.; Roshko, V.; Roshko, V.; Roshko, V. (Theriologia Ukrainica, 2019)
The mammal collection of the Zoological Museum of Uzhhorod University consists of more than 4 800 specimens of 125 mammal species of world fauna. Among them, 115 mammal species are displayed in the exhibition halls. The mammal collection of the Zoological Museum is kept in scientific repositories, while a part of specimens is represented in three exhibition halls (210 exhibits). The geographic origin of specimens in the museum’s collection covers all continents but Antarctica. Most of the species represented in the exhibition (34 or 29.6 %) belong to Rodentia, followed by species of Carnivora (28 or 24.4 %) and Artiodactyla (15 or 13.0 %). The most common species in the collection are rodents (Rodentia): common vole (Microtus arvalis) and striped field mouse (Apodemus agrarius), a total of 1422 specimens. The general systematic representativeness of the exhibited part of the collection of mammals of the Carpathian region is 80 species, which is 77.2 % of the total number of mammals of the Ukrainian part of the Carpathians. In a systematic regard, the mammal collection of the Zoological Museum includes specimens of 125 species of 14 orders of the world fauna (41.2 %), representing 44 families and 89 genera. The collection contains 38 species listed in the Red Data Book of Ukraine, most of them belong to Chiroptera (9 species), Rodentia (9 species), and Carnivora (8 species). All bat species are listed in the Red Data Book of Ukraine. There are 497 bat specimens in the Zoological Museum, 13 of which are displayed in the exhibition halls. The IUCN Red List of Threatened Species, which covers six categories of conservation status, is additionally noted. The rarest species having endangered status (Endangered, EN) are the Russian desman (Desmana moschata), Malayan tapir (Tapirus indicus), tiger (Panthera tigris), Caspian seal (Phoca caspica), barbary macaque (Macaca sylvanus), Asian elephant (Elephas maximus), and European rabbit (Oryctolagus cuniculus). Some other species are critically endangered (CR): Chinese pangolin (Manis pentadactyla), European mink (Mustela lutreola), saiga antelope (Saiga tatarica), and Bornean orangutan (Pongo pygmaeus).